Rebranding dalam Pengembangan Wisata Alam di Desa Selumbung Karangasem - I Dewa Gede Putra Sedana; Ni Luh Putu Ening Permini; Cok Gde Agung Kusuma Putra (BADAN PENERBIT STIEPARI PRESS, 2023)
A tourist village is a form of integration between attractions, accommodation and supporting facilities presented in a structure of community life that is integrated with the prevailing procedures and traditions. Creative economic tourism potential such as honey beekeeping and Virgin Coconut Oil (VCO) production. Even though it has diverse tourism potential, in fact village tourism access support and facilities are still not optimal. Apart from developing access and tourist facilities, the lack of sensitivity to the potential for cultural tourism has also resulted in cultural tourism in Selumbung Village not being able to develop as well as natural tourism potential, but also cultural uniqueness and characteristics. In planning it is considered necessary to carry out planning, namely media planning (determining goals, strategies, programs and media budgeting), FGDs, program outreach). This step is then followed by branding activities, which include: public relations, promotion, tourism exhibitions, creation of social media and websites. It is hoped that the assistance provided by tourism development in Selumbung Village can run as expected.